2020
DOI: 10.1002/eat.23425
|View full text |Cite
|
Sign up to set email alerts
|

Disordered eating attitudes and body shape concerns among North Indian Kathak dancers

Abstract: Objective To determine the prevalence and association between disordered eating attitudes and body shape concerns in a sample of North Indian Kathak dancers. Method Participants were 206 Kathak female dancers and 235 healthy controls, ages 18–45 years. Participants completed questionnaires assessing demographics, disordered eating attitudes, and body dissatisfaction. Pearson correlations assessed the association between the disordered eating attitudes and body dissatisfaction, and binary logistic regression id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Previous research has demonstrated that dancers express more concerns about their physical appearance and body image, which, according to them, have an impact on how they control their dietary intake and eating habits continuously, to lose or maintain weight (32). Accordingly, Kulshreshtha et al (33) showed a positive correlation between body dissatisfaction and disordered eating attitudes, concluding that dancers who are more concerned with body shape size were five times more likely to report disordered eating attitudes than their peers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has demonstrated that dancers express more concerns about their physical appearance and body image, which, according to them, have an impact on how they control their dietary intake and eating habits continuously, to lose or maintain weight (32). Accordingly, Kulshreshtha et al (33) showed a positive correlation between body dissatisfaction and disordered eating attitudes, concluding that dancers who are more concerned with body shape size were five times more likely to report disordered eating attitudes than their peers.…”
Section: Discussionmentioning
confidence: 99%
“…Literature shows that when compared with non-dancers, dancers have a higher risk of developing EDs, disordered eating attitudes, more dieting behaviors, and more binge-eating episodes ( 32 , 33 ). Moreover, compared to other dance genres (contemporary, flamenco, and Spanish dance), ballet dancers are more likely to appoint their coaches as a key factor in their body dissatisfaction, and to report more pressure from choreographers ( 14 , 35 ), an issue that has also been brought up by the dancers in the focus groups, when they talked about how common it was for coaches to talk about their bodies.…”
Section: Discussionmentioning
confidence: 99%
“…This association was also significant for the normal weight participants in our study, in contrast to findings from Dell’Osso and colleagues (2018), who reported a higher rate of ON in those with low BMI than in those with normal or high BMI (42.8% vs. 34.2%) [ 34 ]. Previous studies documented that disordered eating behaviors, attitudes, and body dissatisfaction were highly correlated among professional dancers, indicating that any increase in body shape concerns may directly affect the risk of adopting disordered eating attitudes and behaviors [ 11 ]. Camci and colleagues (2009) [ 30 ] suggested that body image dissatisfaction and forms of EDs, such as AN and bulimia, are more common in ballet dancers, as they face strong occupational pressure to be thin, and their practice of intensive exercise in combination with diet can lead to ED [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies mentioned that dancers are three-times more likely than their non-dancer counterparts to develop an ED. Kulshreshtha and colleagues (2020) found that approximately 83% of dancers reported body shape concerns, ED behaviors, or the use of a non-healthy weight regulation strategy [ 11 ]. Many dancers have a distorted body image, linked with the induction of ED [ 12 ] and the development of body dissatisfaction [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation